The Effect Of Persuasive Communication By Teachers On The Learning Motivation Of Students Of Class During The Covid-19 Pandemic - Andre Mahendra (Journal of Media and Communication | E-ISSN : 3063-9581, 2024)
The spread of the coronavirus pandemic or Covid-19 has provided its own challenges for educational institutions in Indonesia, one of which is SMKN 1 West Sumatra is one of the vocational education institutions in Padang City. In the online learning process, many students do not understand the material taught by the teacher and there is a problem of declining grades in students. When students are in a condition of not having motivation to learn, this is where the role of teachers to provide motivation to students is with persuasive communication techniques. The purpose of this study is to reveal proportionally the influence of teachers' persuasive communication on the learning motivation of students of SMKN 1 West Sumatra during the Covid-19 pandemic. This study uses a type of quantitative research. The sampling technique is a simple random sampling technique. The sample of this study is class X students of SMKN 1 West Sumatra which totals 84 students. A simple linear regression analysis was used to test the hypothesis with the SPSS 24 program. The results of this research show that the Persuasive Communication variable of the Teacher Persuasive Communication category is quite good. The results indicate that there is an influence between teachers' persuasive communication and students' motivation to learn during the Covid-19 pandemic. Learning activities in the teacher's classroom tend to use persuasive communication, to direct student behavior in the teacher's classroom to apply a democratic and permissive discipline model. Teachers do not give heavy sanctions, but are more dominant in the directions and advice that motivate students to be better.